2014
DOI: 10.3390/w6102929
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Determinants of Residential Water Demand in Italy

Abstract: Abstract:The aim of this study was to estimate the determinants of residential water demand for chief towns of every Italian province, in the period 2007-2009, using the linear mixedeffects model estimated with the restricted-maximum-likelihood method. Results confirmed that the applied tariff had a negative effect on residential water consumption and that it was a relevant driver of domestic water consumption. Moreover, income per capita had a positive effect on water consumption. Among measured climatic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 60 publications
5
42
0
2
Order By: Relevance
“…These results could be compared with others in the Mediterranean European Area such as the study conducted by Romano et al [23]. In this regard, the aim of this study was to estimate the determinants of residential water demand for the chief towns of every Italian province (2007-2009), using the linear mixed-effects model estimated with the restricted-maximum-likelihood method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results could be compared with others in the Mediterranean European Area such as the study conducted by Romano et al [23]. In this regard, the aim of this study was to estimate the determinants of residential water demand for the chief towns of every Italian province (2007-2009), using the linear mixed-effects model estimated with the restricted-maximum-likelihood method.…”
Section: Discussionmentioning
confidence: 99%
“…Further research is needed on the role of utility ownership because it remains unclear whether changes in governance toward a larger presence of non-public actors have by themselves led to improved water-conservation practices and, therefore, to reductions in water consumption [32]. This lack of clarity is due to the fact that reductions in water consumption seem to affect cities with different systems of water ownership and management [23].…”
Section: Introductionmentioning
confidence: 99%
“…Hoffmann et al () use the number of rainy days and the number of warm days in each quarter (those with a daily maximum in the uppermost quartile of all daily temperatures) and find a significantly negative impact on water demand. Romano et al () find no influence of temperature while estimating the average consumption of drinking water for domestic use; however, they showed that precipitation exerts a significant negative effect on overall water consumption. Maidment and Miaou () show the nonlinear effect of weather variables in water demand using daily water use data.…”
Section: Introductionmentioning
confidence: 99%
“…Water has been considered as a natural resource that has utilization value but little economic value. As the pressure and demand for water supply increase, the recognition of the economic value of water resources and hence water pricing procedures attracts more attention to meet the imbalance between water supply and demand (Mitchell, 1984; Arbuésa et al, 2003; Wodraska, 2006) even for areas with abundant water resources. Water pricing procedures try to adopt the marginal cost pricing strategy to allocate water to the most valuable needs and consequently reduce the ultimate water-use (Agthe and Billings, 1986).…”
Section: Introductionmentioning
confidence: 99%